Wildhorse [compact disc] - RaeLynn, 1994- (Warner Music Nashville, 2017)
RaeLynn has been waiting a long time to share more of her life story. With the release of her debut album, the second season finalist from The Voice gets to do just that. Includes the single Love Triangle.